Analysis of Factors Influencing XYZ University Lecturer's Intentions in Use of Microsoft Teams in the Post-Pandemic Period Using the UTAUT2 Approach - Salainti, Shane Stephen Dylan; Walean, Ronny Hansje (PT Mattawang Mediatama Solution, 2025)
The post-pandemic era has brought significant challenges and opportunities for the adoption of digital platforms in education. This study investigates the factors influencing the intention and behavior of lecturers at XYZ University in using Microsoft Teams, utilizing the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. Key constructs examined include Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FC), Hedonic Motivation (HM), Learning Value (LV), and Habit (HT). Data were collected through a structured questionnaire distributed to lecturers and students with prior experience using Microsoft Teams and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Behavioral Intention, Facilitating Conditions, and Habit significantly influence Use Behavior, while the one that significantly influence Behavioral Intention is just Habit alone. Behavioral Intention emerged as a strong predictor of Use Behavior, demonstrating the central role of intention in technology adoption. The study highlights the importance of usability, emotional engagement, and institutional support in fostering sustained adoption of Microsoft Teams. Recommendations for enhancing adoption include improving training programs, ensuring adequate technical support, and integrating features that align with teaching goals and preferences.